ベストアンサー

NEW! この回答はいかがでしたか? リアクションしてみよう

その他の回答(3件)

[√{x(x+1)}-√x]/x=√x{√(x+1)-1}/x={√(x+1)-1}/√x ={√(x+1)-1}{√(x+1)+1}/[√x{√(x+1)+1}] ={(x+1)-1}/[√x{√(x+1)+1}]=x/[√x{√(x+1)+1}]=√x/{√(x+1)+1} ∴ 求める極限値=0/2=0

lim[x→+0](√(x(x+1))-√x)/x =lim[x→+0](√(x²+x)-√x)/x =lim[x→+0](√(1+1/x)-√(1/x)) 1/x=tと置換 x→+0のときt→∞ =lim[t→∞](√(1+t)-√t) =lim[t→∞](√(1+t)-√t)•(√(1+t)+√t)/(√(1+t)+√t) =lim[t→∞](1+t-t)/(√(1+t)+√t) =lim[t→∞]1/(√(1+t)+√t) =0

画像

lim x→+0 ‪(√‬[x(x+1)]-‪√‬x)/x =‪(√‬[x(x+1)]-‪√‬x)‪(√‬[x(x+1)]+‪√‬x)/x‪(√‬[x(x+1)]+‪√‬x) =x/‪(√‬(x^2+x)+‪√‬x) =x/2+x+o(x) ->0